The ceramic art of James Tower - Wilcox, Timothy (Lund Humphries, 2012)
James Tower (1919-88) is widely regarded as one of the most distinctive figures in post-war British ceramics. This book provides a comprehensive visual document of Tower's work, incorporating a complete illustrated catalogue. It also includes a detailed biography, setting Tower in the social and artistic context in which he lived and worked.